Meningkatkan Hasil Belajar Pak dengan Model PBL Materi Aku Memiliki Kemampuan dan Keterbatasan pada Siswa Kelas VII SMPN. 4 Satu Atap STTU Julu - Juni Arma Br Malau; Yohanes Umbu Lede; Paulus Asriadi (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research is aimed to improve the teaching learning process and learning outcomes of Catholic Religious Education and Characters through the Problem Based Learning model. This research is Classroom Action Research. The subjects of the research were the tenth students of the seventh grade of SMP Negeri 4 Satu Atap STTU Julu academic year of 2024/2025. The data analysis technique is descriptive analysis consisting of students’ affective learning outcomes data and students’ cognitive learning outcomes data through observation and written tests. The research was conducted in two cycles. The result of the research shows that the percentage of the students’ completeness has increased in each cylce which is 60% to 80%, and the degree of students’ participation in the learning process has increased from 50% to 80%. It can be concluded that the Problem Based Learning model improves the learning outcomes in Catholic Religious Education and Characters of the seventh grade students in SMP Negeri 4 Satu Atap STTU Julu in the topic of I have Ability and Inability.